The effects of Pseudomonas aeruginosa quorum sensing signalling molecules on human T cell function - Huynh, Tina (2008)
Quorum sensing signalling molecules (QSSMs) are important to Pseudomonas aeruginosa virulence and biofilm development which aid establishment and persistence of these bacteria in the host. Recent progress in quorum sensing (QS) research has demonstrated that the two QSSMs, 3-oxo-C12-HSL and PQS interact with eukaryotic cells and modulate immune responses. Early research has indicated these two QSSMs are immunosuppressive, and because T cells play an important role in defending the host against the attack of P. aeruginosa (Stevenson et al., 1995), this warrants investigations into the interactions between QSSMs and T cells.